PENGARUH TINGKAT PEMAHAMAN PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DI KABUPATEN TAKALAR - Atia Kirana W; Usri Usran (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2021)
The purpose of this research is to examine the characteristics of tax understanding and tax significance on taxpayer compliance. The population of this research is taxpayers who are registered at the takalar district tax office with a total sample of 100 people who can be respondents. The analytical method used is descriptive statistics and multiple linear regression analysis. This study used a data collection method in the form of a questionnaire method. The data were analyzed using the SPSS statistical program The results of this study explain that there is no significant influence between the tax understanding variable on taxpayer compliance while the tax sanction variable has a positive and significant effect on tax pay compliance. The test results obtained by the coefficient of determination the adjusted R square value is 0.466. This shows that 46.6% of taxpayer compliance is influenced by the variation of the two variables, namely tax understanding (X1) and tax sanctions (X2). While the remaining 53.4% ​​is influenced by other variables which are not researched. The results of data analysis support the research hypothesis which states that tax understanding has a positive effect on taxpayer compliance at the tax office in Takalar district. The results of data analysis support the research hypothesis which states that tax sanctions have a positive effect on taxpayer compliance. While the results of the analysis of the standardized beta coefficient test, it is known that the value of the standardized beta coefficient (ß) of the Tax Sanctions variable (ß1) is 0.682 greater than the standardized beta coefficient of the Tax Understanding variable (ß2) of 0.034. Thus it can be said that the Tax Sanctions variable has a dominant influence on taxpayer compliance. So that the Tax Sanctions hypothesis testing has a dominant influence on taxpayer compliance at the Tax Office in Takalar Regency.